Revealing unusual chemical bonding in planar hyper-coordinate Ni2Ge and quasi-planar Ni2Si two-dimensional crystals1. Issue 39 (21st October 2015) - Yang, Li-Ming; Popov, Ivan A.; Frauenheim, Thomas; Boldyrev, Alexander I.; Heine, Thomas; Bačić, Vladimir; Ganz, Eric
<x xml:space="preserve">Abstract</x> We predict two novel highly stable 2D planar hexacoordinate monolayer sheets Ni2Si and Ni2Ge with unusual chemical bonding.